The Echo Chamber Phenomenon and It's Effect in Community Empowerment Practice - Muhammad Ilham Fahmi; Unggul Yoga Ananta; Helly Octilia (Asian Social Work Journal, 2022)
The existence of closed communication patterns between individuals in groups describes the phenomena of echo chamber, which is a form of communication in which a person only hears to the same opinion as he thinks. If there is polarization of opinion among groups in society, this phenomena will become a problem. As a result, macro social workers must see this occurrence as a potential threat in their work. The purpose of this research is to define the echo chamber phenomena and its implications for community empowerment. The issues of community empowerment practices carried out by social workers in Cigugur Girang village are described in this study using a qualitative approach and a case study method. The findings conclude that the echo chamber effect can arise among persons who are in conflict. The conflict causes societal polarization, which has an impact on macro social worker practice. It's tough for social professionals to find a place amid polarized groups. As a result, the empowerment goal will be hampered.